Investigation of hydrodynamics in bubble column with internals using radioactive particle tracking (RPT). Issue 11 (23rd June 2017) - Kalaga, Dinesh V.; Pant, H. J.; Dalvi, Sameer V.; Joshi, Jyeshtharaj B.; Roy, Shantanu
Abstract : Even though many experimental investigations are reported on this subject of liquid velocity patterns in bubble columns, most of the reported work is restricted to measurements at the near wall regions, columns without internals, and in low dispersed phase hold‐ups. In the present work, a non‐invasive radioactive particle tracking technique was employed to quantify the hydrodynamic parameters in 120 mm diameter bubble column with, and without vertical rod internals, using air/water system as the working fluids. The superficial air velocities cover a wide range of flow regimes: from 14 to 265 mm/s. Experiments were performed for two internals configurations with percentage obstruction area varied from 0 (without internals) to 11.7%. We report that the liquid phase hydrodynamics depends strongly on superficial gas velocity and internals. © 2017 American Institute of Chemical Engineers AIChE J, 2017